The Dynamics of Character Building in Adolescents Through Spiritual Strengthening: A Comparative Study in Two Orphanages - Adelina, Ria; Tanjung, Muaz (Madania: Jurnal Ilmu-Ilmu Keislaman, 2025)
This study aims to analyze and compare the dynamics of moral development for adolescents through a spiritual approach at the Al-Wasliyah Orphanage and the Muhammadiyah Orphanage in Medan City. The study focuses on the approach, methods, results of coaching, and supporting and hindering factors faced by each orphanage. The research was conducted using a qualitative approach and comparative analysis of data from interviews and observations. Data were collected through interviews and observations of eight informants, consisting of the orphanage head and resident adolescents. The findings reveal that Al-Wasliyah emphasizes habituation and moral modeling through the emotional relationship between caregivers and children, hile Muhammadiyah adopts a more structured, institutional approach involving collective evaluation. This difference creates dynamics in the indicators of moral success: Al-Wasliyah assesses through worship practices and personal attitudes, while Muhammadiyah does so through staff participation and reports The study emphasizes the need to integrate affective and structural strategies in adolescent moral development. Practically, this research offers insights for orphanage managers to design reflective.